Ni-2[Lncl(6)] (Ln = Eu-Ii, Ce-Ii, Gd-Ii): The First Ln(Ii) Compounds Stabilized in a Pure Inorganic Lattice - Venegas-Yazigi, D; Venegas-Yazigi, D (ROYAL SOC CHEMISTRY, 2018)
Here we report the first examples of 3d-4f compounds based on Ln(II) cations. We have obtained a series of Ni-2[LnCl(6)] isostructural compounds where Ln(II) = Ce 1, Eu 2 and Gd 3 which were characterized in a cubic crystalline system with a Fm3m space group. Magnetic and optical characterization was also performed on this new class of compounds.